Ontogenesis of Tissue Plasminogen Activator in the Human - Åstedt, B; Pandolfi, M (Thrombosis and Haemostasis, 1971)
The ontogenesis of tissue plasminogen activator in various tissues was studied in 10 embryos and 58 foetuses with a histochemical method.The first appearance of activator activity was seen in a 4-weeks old embryo. At 8-9 weeks it was seen in the eye, meninges, heart, lungs, kidney and vena cava. In the foetal heart high activity was found in the coronary vessels, which can be regarded as the vasa vasorum of the heart. In the lungs a moderate activity increased at 24 weeks of age, when vascularisation increases more rapidly. Intense activity was seen in the highly vascularized corneoscleral junction of the eye later involved in the drainage of aqueous humor.In the kidney the activity could be related to the vessels, while no activity was seen in the glomeruli, the collecting system or the pelvis. In the vessels the activator activity was fairly high. No activity was seen in any stage of development of the liver.The plasminogen activator activity may be of importance for maintaining the foetomaternal circulation and micro-circulation in rapidly growing foetal organs. In the embryo the enzyme pattern is dominated by protein synthetizing enzymes. During foetal development the enzyme pattern changes owing to supervention of enzymes necessary for the function of the various organs. Plasminogen activator belongs to this latter group. The appearance of plasminogen activator activity may therefore be regarded mainly as a sign of functional maturity of the foetal organs.